Методика віддаленого визначення версії MySQL сервера за допомогою пакета Kali Linux - Гонтарь, І. А.; Снігуров, А. В. (ХНУРЕ, 2023)
A database is a storage for any information that should be stored and proceeded. A large number of services work directly with the database. It is deployed on the servers on which the database works, for example, on a Linux server. The information that is stored on the server is a potential target for attackers. In order to have access to the server, you need to pass the configuration of the server, and then get access to the database. The correct configuration of servers and services allow reducing the risks of any malicious actions, but even a small piece of information, i.e. a version of servers or services, can become a critical vulnerability, because each version of the operating system or software can contain critical vulnerabilities that can be closed only in new versions. Therefore, such information as the server or service version can be used for malicious actions.
Keywords: пакет Kali Linux; кібербезпека